2014
DOI: 10.1186/ar4474
|View full text |Cite
|
Sign up to set email alerts
|

Survivin but not Fms-like tyrosine kinase 3 ligand is up-regulated before the onset of rheumatoid arthritis: a pilot study

Abstract: IntroductionAntibodies against citrullinated peptides (anti-CCP) and increased levels of cytokines precede the development of rheumatoid arthritis (RA) by several years. Recently, the proteins survivin and Fms-like tyrosine kinase 3 ligand (Flt3L) have been identified as biomarkers of RA associated with joint destruction. Our objective was to investigate the potential of survivin and Flt3L as predictors of RA in samples from patients prior to onset of symptoms.MethodsThis study included 47 individuals sampled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
23
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 33 publications
(45 reference statements)
3
23
1
2
Order By: Relevance
“…Like others, we have previously shown that Flt3L is enriched in the serum of patients with RA and that this protein accumulates in the synovial fluid of arthritic joints [30][31][32]. In addition, Flt3L has been suggested as a useful serological marker at early stages of RA [33].…”
Section: Introductionsupporting
confidence: 61%
See 1 more Smart Citation
“…Like others, we have previously shown that Flt3L is enriched in the serum of patients with RA and that this protein accumulates in the synovial fluid of arthritic joints [30][31][32]. In addition, Flt3L has been suggested as a useful serological marker at early stages of RA [33].…”
Section: Introductionsupporting
confidence: 61%
“…The presence of Flt3 + cells in the synovial tissue of patients with RA and the potential involvement for Flt3L in OC differentiation suggest that Flt3L may contribute to the severe bone damage that occurs during RA [31]. This hypothesis is further supported by the increased levels of Flt3L in the serum and synovial fluid of patients with RA showing high correlation to TNF-a, IL-1b, and IL-6, cytokines known to potentiate OC differentiation [32]. Accordingly, local knee exposure to Flt3L aggravates arthritis in mice [30].…”
Section: Introductionmentioning
confidence: 87%
“…A pilot study on the Medical Biobank of Northern Sweden showed that survivin was increased in individuals before clinical onset of RA. Importantly, survivin correlated with the cytokines driving formation of Th1 and Th17 proinflammatory effector T cells at the initial stages of RA [2]. In the experimental setting, survivin is shown critical for the process of antigen presentation; the break point of immune responses in RA, as it is required for the fms-related tyrosine kinase 3-dependent maturation of dendritic cells; and expression of the MHCII receptor [14,15].…”
Section: Introductionmentioning
confidence: 94%
“…Survivin, the smallest member of the inhibitor of apoptosis protein family, has emerged recently as a biomarker of RA [2]. It is a multifunctional protein that plays biologic roles in apoptosis and the cell cycle.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have reported high expression of total survivin in RA synovial fibroblast cells, peripheral blood mononuclear cells (PBMCs), serum, and synovial fluid which correlated with disease activity and joint destruction . Increased serum levels of survivin correlated with expression of Th1 and Th17 pathogenic cytokines in RA patients . Serum survivin led to increased expression of α‐chains of β2‐integrins on leukocytes, suggesting contribution of survivin to the enhanced infiltration of pathogenic immune cells to the sites of inflammation in RA patients.…”
Section: Introductionmentioning
confidence: 99%